International students’ academic adjustment in Private Universities in Malaysia - Safrena Noreen Abd Malek,; Abdul Latiff Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia is known for having a mixed population with diverse backgrounds and religions living in peace. Malaysian education systems opened their doors to foreign countries in 1996, allowing for the establishment of branch campuses, and the private education system entered our educational sector. Since then, many international students have travelled to Malaysia to study. According to the Star Online in 2019, Malaysian higher education institutions have registered more than 170,000 international students from over 135 countries for their intercultural adaptation experiences. The top three countries are from Bangladesh, Indonesia, and China. This qualitative study investigates the academic adjustment experiences of international students in private universities in Malaysia through the lens of Cross-Cultural Adaptation (CCA) theory. Employing in-depth interviews, the research seeks to unveil the intricate processes, challenges, and adaptive strategies that shape the academic trajectories of international students within the Malaysian higher education landscape. The study aims to explore how cultural, linguistic, and academic factors influence the academic adaptation of international students. Through purposive sampling, participants will share their personal narratives, shedding light on the dynamic interplay between cultural nuances and the pursuit of academic success. Thematic analysis of the qualitative data will uncover patterns and insights into the ways in which international students negotiate academic challenges and integrate into the Malaysian educational milieu. The findings aim to contribute to the broader understanding of cross-cultural adaptation in academic settings, providing context-specific knowledge that can inform institutional policies and practices to foster a more inclusive and supportive environment for international students in Malaysian private universities.